Stereotip dan Penolakan Indekos Mahasiswa Asal Papua di Salatiga - Kristina Roseven Nababan (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
Education has the potential to increase human resources. In this case, students from Papua are attempting to improve their quality of life by furthering their education in the Java city of Salatiga. However, efforts to continue education were hampered by social discrimination, particularly in selecting a house in Salatiga. This paper aims to identify Papuan student stereotypes that lead to the boarding house. This study uses qualitative methods with a phenomenological approach, with primary data gathered through interviews and observations of Papuan and West Papuan students, and secondary data collected through library research. The findings revealed four stereotypes that contributed to Papuan students' rejection in Salatiga. Both Papuan students and Salatiga people contribute to these stereotypes through a lack of recognition, communication, language, and cultural adaptation. Prejudice, as well as structural and cultural violence, result from this. As a result, stakeholders must actively participate in conflict resolution efforts through peacebuilding and peacemaking.